1997
DOI: 10.1007/s002239900240
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Bone Mass in Women after Bone Marrow Transplantation

Abstract: Osteoporosis is a common disease among patients undergoing transplantation. Its prevalence and complications have been well described in solid organ recipients, especially kidney, liver, and heart. However, studies in bone marrow transplantation (BMT) are scarce. Among the mechanisms invoked in the pathogenesis of BMT osteoporosis are the baseline disease, the use of immunosuppressive drugs and, more remarkably, secondary hypogonadism. We present a study of 27 women who underwent BMT, all of them suffering ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…In a very recent cross-sectional study, 51% of the patients fulfilled the BMD criteria of osteopenia at least in the lumbar spine 3 years after BMT. 6 Note that the majority of our patients had a reduced bone mass even at the beginning of the study. The basic hematologic malignancy together with its treatment offer a conceivable explanation for the finding.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a very recent cross-sectional study, 51% of the patients fulfilled the BMD criteria of osteopenia at least in the lumbar spine 3 years after BMT. 6 Note that the majority of our patients had a reduced bone mass even at the beginning of the study. The basic hematologic malignancy together with its treatment offer a conceivable explanation for the finding.…”
Section: Discussionmentioning
confidence: 77%
“…5 After BMT the most harmful drugs for the bone are corticosteroids and cyclosporine used for prophylaxis and treatment of graft-versus-host disease (GVHD). 5 Prevalence of osteoporosis among bone marrow transplant recipients has been studied only in two cross-sectional studies; 2,6 no longitudinal study of bone mass changes after transplantation is available. In the only study concerning treatment of BMT-associated osteoporosis, estrogen replacement therapy (HRT) increased bone mass in 13 women who started treatment on average 13 months after BMT.…”
mentioning
confidence: 99%
“…30 The administration of steroids to treat GVHD and GVHD itself may be another possible explanation for the decreased osteoblastic activity following a BMT. 9 A previous study observed a negative correlation between the serum osteocalcin level and the mean daily dose of steroids that were administered during the 3 months after a BMT. 8 This study also observed a significant correlation between the cumulative steroid dose and bone loss in the lumbar and proximal femoral bones during the first year after a BMT.…”
Section: Discussionmentioning
confidence: 94%
“…It was previously reported that bone disease is one of the complications of a BMT. 1,5 According to Castaneda et al, 9 33 and 18% of BMT recipients had osteopenia and osteoporosis in the lumbar spine when examined 33.6 months after BMT. The main causes of bone loss following a BMT include the use of immunosuppressants and hypogonadism induced by TBI or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been described after hematopoietic stem cell transplantation (SCT) as well, with the majority of cases reported in alloSCT recipients. [7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] AlloSCT-associated BMD loss is usually described in the first 6-12 months after the transplantation, but varies widely from 40 days 17 to 4-6 years after the transplantation, 30,31,34 and in some instances can persist for 10-12 years. 26,28 Baseline BMD pre-SCT is usually within the normal limits; [15][16][17]24,[27][28][29][30]33 the few exceptions noting high O/O prevalence pre-SCT are probably due to the underlying diseases or intensive chemotherapy prior to the transplantation.…”
Section: Introductionmentioning
confidence: 99%